2009
DOI: 10.1051/0004-6361/200912950
|View full text |Cite
|
Sign up to set email alerts
|

The hyperfine structure of the inversion-rotation transitionJK= ${1}_{0}$ $\leftarrow$ ${0}_{0}$ of NH3investigated by Lamb-dip spectroscopy

Abstract: The ground-state inversion-rotation transition of ammonia at 572.498 GHz has been investigated in the laboratory using a sourcemodulation microwave spectrometer equipped with a double-pass cell. The experiment has been carried out at a pressure lower than 0.5 mTorr, thus enabling to record a Lamb-dip spectrum showing a partial resolution of the magnetic hyperfine structure due to the three proton spins. The achieved high resolution proved to be comparable to that of molecular beam experiments. This measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…1 together with the hyperfine structure from Table 3 of Cazzoli et al (2009), adopting the Local Standard of Rest (LSR) velocity (V LSR ) of L1544, 7.2 km s −1 , as reported by Tafalla et al (1998). This is the first observed interstellar o-NH 3 (1 0 −0 0 ) spectrum clearly showing the main groups of hyperfine components.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…1 together with the hyperfine structure from Table 3 of Cazzoli et al (2009), adopting the Local Standard of Rest (LSR) velocity (V LSR ) of L1544, 7.2 km s −1 , as reported by Tafalla et al (1998). This is the first observed interstellar o-NH 3 (1 0 −0 0 ) spectrum clearly showing the main groups of hyperfine components.…”
Section: Resultsmentioning
confidence: 54%
“…1. We took into account the hyperfine structure, produced by the electric quadrupole coupling of the N nucleus with the electric field of the electrons, as well as the magnetic hyperfine structure that is due to the three protons (Cazzoli et al 2009). The hyperfine collision rate coefficients were taken from the recent calculations of Bouhafs et al (2017), which, for the first time, include the non-spherical structure of p-H 2 (the main form of H 2 in cold molecular gas, Flower et al 2006;Brünken et al 2014), so that they differ (by up to a factor 2) from those of Maret et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…A review on ammonia is found in Ho & Townes (1983) and an investigation of the hyperfine structure components of the rotational transitions has been performed by Coudert & Roueff (2006) and of ortho-NH 3 at 572 GHz by Cazzoli et al (2009).…”
Section: Transition Frequencymentioning
confidence: 99%
“…Müller et al (1999). A review on ammonia is found in Ho & Townes (1983), and an investigation of the hyperfine structure components of ortho-NH 3 at 572 GHz was recently performed by Cazzoli et al (2009). NH + measurements have been made by Verhoeve et al (1986) and Hübers et al (2009).…”
Section: Observations and Data Reductionmentioning
confidence: 99%